Metabolic Characteristics in Meal of Black Rapeseed and Yellow-Seeded Progeny of Brassica napus–Sinapis alba Hybrids - Jinjin Jiang; Yue Wang; Tao Xie; Hao Rong; Aimin Li; Yujie Fang; Youping Wang (Molecules, 2015)
Breeding of yellow-seeded rapeseed (Brassica napus) is preferred over black-seeded rapeseed for the desirable properties of the former. This study evaluated the metabolites and nutritive values of black-seeded rapeseed meal and yellow-seeded meal from the progeny of a B. napus–Sinapis alba hybrid. Yellow-seed meal presented higher protein (35.46% vs. 30.29%), higher sucrose (7.85% vs. 7.29%), less dietary fiber (26.19% vs. 34.63%) and crude fiber (4.56% vs. 8.86%), and less glucosinolates (22.18 vs. 28.19 μmol/g) than black-seeded one. Amounts of ash (3.65% vs. 4.55%), phytic acid (4.98% vs. 5.60%), and total polyphenols (2.67% vs. 2.82%) were decreased slightly in yellow-seeded meal compared with black-seeded meal. Yellow-seeded meal contained more essential amino acids than black-seeded meal. Levels of the mineral elements Fe, Mn, and Zn in yellow-seeded meal were higher than black-seeded meal. By contrast, levels of P, Ca, and Mg were lower in yellow-seeded meal. Moreover, yellow-seeded meal showed lower flavonol (kaempferol, quercetin, isorhamnetin, and their derivatives) content than black-seeded meal. Comparison of metabolites between yellow and black rapeseed confirmed the improved nutritional value of meal from yellow-seeded B. napus, and this would be helpful to the breeding and improvement of rapeseed for animal feeding.